2011
DOI: 10.1111/j.1349-7006.2011.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos surface provides a niche for oxidative modification

Abstract: Asbestos is a potent carcinogen associated with increased risks of malignant mesothelioma and lung cancer in humans. Although the mechanism of carcinogenesis remains elusive, the physicochemical characteristics of asbestos play a role in the progression of asbestos-induced diseases. Among these characteristics, a high capacity to adsorb and accommodate biomolecules on its abundant surface area has been linked to cellular and genetic toxicity. Several previous studies identified asbestos-interacting proteins. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
79
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 65 publications
1
79
0
2
Order By: Relevance
“…We hypothesized that appropriate intervention may reduce free radical generation even after exposure to asbestos fibers. This is because generation of free radicals largely depends on catalytic iron (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that appropriate intervention may reduce free radical generation even after exposure to asbestos fibers. This is because generation of free radicals largely depends on catalytic iron (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Crocidolite and amosite contain abundant iron in mineral contents. In contrast, chrysotile can adsorb iron (heme from hemoglobin) on its surface through hemolytic activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Asbestos bodies are representatives of corpses of macrophages, indicating that numerous thin and long asbestos fibers presumably passed through the lung parenchyma. Our data demonstrated the high affinity of hemoglobin to asbestos, forming a niche for oxidative reactions 5. (iv) We believe that catalytic Fe(II) is more important than Fe(III) in carcinogenesis because it initiates a Fenton reaction, whereas Fe(III) is almost insoluble at neutral pH.…”
mentioning
confidence: 62%
“…(ii) The origin of iron is an interesting issue. We suggested the importance of hemolysis and the adsorption thereafter of hemoglobin on asbestos fibers in the lung 5. Alternatively, the recent cutting‐edge mineralogical studies by Dr Gualtieri clearly showed the components/localization of iron on asbestos1 and are of much interest for further consideration.…”
mentioning
confidence: 93%
“…8,9 The currently proposed three major hypotheses regarding the pathogenesis of asbestos-induced MM can be summarized as follows: 10 (1) the 'oxidative stress theory' is based on epidemiological studies showing that asbestos fibers containing iron are more carcinogenic, 11 and the fibers catalyze the generation of reactive species; 12,13 (2) the 'chromosome tangling theory' postulates that asbestos fibers damage chromosomes when mesothelial cells divide; 14,15 (3) the 'theory of adsorption of specific proteins as well as carcinogenic molecules' states that proteins and chemicals, such as components of cigarette smoke, are attached to the asbestos surface in vivo. 15 Notably, these hypotheses are based on asbestos being able to enter mesothelial cells, and these complexes could be involved in the pathogenesis. 16 In addition, chronic inflammation is suggested to be the hallmark of asbestos deposition in tissue, although it may contribute to asbestos-related carcinogenesis by the mechanisms mainly related to hypothesis 1.…”
mentioning
confidence: 99%